A New Route to Cyclohexanone using H2CO3 as a Molecular Catalytic Ligand to Boost the Thorough Hydrogenation of Nitroarenes over Pd Nanocatalysts. Issue 12 (15th May 2019) - Zhao, Tian‐Jian; Zhang, Jun‐Jun; Zhang, Bing; Liu, Yong‐Xing; Lin, Yun‐Xiao; Wang, Hong‐Hui; Su, Hui; Li, Xin‐Hao; Chen, Jie‐Sheng
Abstract: Carbon dioxide has been important in green chemistry, especially in catalytic and chemical engineering applications. While exploring CO2 to produce cyclohexanone for nylon or nylon 66 that is currently produced with low yields using harsh catalytic methods, we made the exciting discovery that carbonic acid, generated from dissolved CO2 in water, was utilized as molecular catalytic ligand to produce cyclohexanone via the hydrogenation of nitrobenzene in aqueous solution that uses Pd catalysts with a total yield higher than 90 %. Importantly, the gaseous nature of catalytic ligand H2 CO3 profoundly simplifies post‐catalysis cleanup unlike liquid or solid catalysts. This new green catalysis strategy demonstrated the universality for hydrogenation of aromatic compounds like aniline and N‐methylaniline and could be broadly applicable in other catalytic field like artificial photosynthesis and electrocatalytic organic synthesis. Abstract : Molecular catalytic ligand CO2, generating carbonic acid (H2 CO3 ) in water, is applied to accelerated the adsorption and following hydrogenation of nitrobenzene on Pd surface by forming two hydrogen bonds. Such an enhanced pre‐adsorption of nitrobenzene boosts the yield of cyclohexanone excess of 90 % on Pd nanocatalysts, promising a new, mild and highly efficient route for the cyclohexanone production than other routes in industrial scale using a reusable molecular ligand for facile separation.